Individually guided neuromodulation in special operator veterans with symptoms of PTSD and traumatic brain injury: preliminary data from a chart review - B. Christopher Frueh; Celeste Crowder; Alexander Taghva; Alexander Taghva (Frontiers in Neurology, 2025)
IntroductionSpecial operations forces (SOF) are at particular risk of suffering from Posttraumatic Stress Disorder (PTSD) and Traumatic Brain Injury (TBI), and often these two conditions are comorbid, with the inciting event causing both conditions. These conditions present with broad-band electroencephalogram (EEG) abnormalities that may be amenable to neuromodulation.MethodsThis retrospective chart review reports on preliminary safety and clinical response data of individualized neuromodulation in a cohort of SOF veterans suffering from symptoms of PTSD and TBI. 33 male SOF veterans with TBI and PTSD symptoms received α-guided repetitive transcranial magnetic stimulation (α-rTMS) 5 days per week, with the magnetic pulse frequency set to their individual alpha frequency (IAF). Data on clinical scale scores at baseline and conclusion of treatment were extracted, including Rivermead Post-Concussion Questionnaire (RPQ), PTSD Checklist for DSM-5 (PCL-5) and side-effects.ResultsThirty-three (33) charts containing pre-post scales for at least one of the clinical measures collected were reviewed. TBI symptom severity decreased an average of 54% on the RPQ (p < 0.01) and PTSD symptom severity decreased an average of 37.6% on the PCL-5 (p < 0.01). For participants with PCL-5 scores above the screening threshold of 33, 69% no longer met clinical criteria for PTSD at the end of the human performance program. Side effects were consistent with those reported for standard TMS, most frequently headache and fatigue.ConclusionSignificant reductions in TBI clinical symptoms as well as significant decreases in PTSD clinical severity were reported in SOF veterans who underwent α-rTMS. Side effects were equivalent to those observed in normal TMS. Data supports the need for α-rTMS clinical trials in the SOF veteran population to further demonstrate the clinical impact of this approach.